(3GdGfJUGQ aj GdQO Ydi GdeYJRdI GdbOQjI GdCTQGQs - (3jMji Hf CHj GdNjQ Hf eMeO Hf ehSi GdYeQGfj SGde Hf SYjO Hf YHO Gddgs
(3ChdgG (B:s
(3Chdg eHJhQ hChd GdehLhO efg bhdg (B: (3hbGd hgPG jOd Ydi EadGSg ef GdYQHjI habO GdJejjR Hjf GdYHGQI Yef jYbd s
(3BNQgG (B:s
(3hcja jLhR YbO GdEeGeI Ydi Mce eNGda ddTQjYI hGddg SHMGfg CYde hHYjHI CMce s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3Ydi MhGTjgG JYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds